미량오염물질 관리를 위한 산화 및 흡착 기반 하수 방류수 강화처리 기술의 연구 동향 및 시사점 - 최상기; 이웅배; 김영모; 홍석원; 손희종; 이윤호 (대한상하수도학회, 2022)
Conventional wastewater treatment plants (WWTPs) do not fully remove micropollutants. Enhanced treatment of sewage effluents is being considered or implemented in some countries to minimize the discharge of problematic micropollutants from WWTPs. Representative enhanced sewage treatment technologies for micropollutant removal were reviewed, including their current status of research and development. Advanced oxidation processes (AOPs) such as ozonation and UV/H2O2 and adsorption processes using powdered (PAC) and granular activated carbon (GAC) were mainly discussed with focusing on process principles for the micropollutant removal, effect of process operation and water matrix factors, and technical and economic feasibility. Pilot- and full-scale studies have shown that ozonation, PAC, and GAC can achieve significant elimination of various micropollutants at economically feasible costs(0.16-0.29 €/m3). Considering the current status of domestic WWTPs, ozonation and PAC were found to be the most feasible options for the enhanced sewage effluent treatment. Although ozonation and PAC are all mature technologies, a range of technical aspects should be considered for their successful application, such as energy consumption, CO2 emission, byproduct or waste generation, and ease of system construction/operation/maintenance. More feasibility studies considering domestic wastewater characteristics and WWTP conditions are required to apply ozonation or PAC/GAC adsorption process to enhance sewage effluent treatment in Korea.